Expression profiling of muscle invasive and non-invasive bladder tumors for biomarkers identification related to drug resistance, sensitivity and tumor progression. Issue 1 (1st January 2020) - Antonova, Olga; Rukova, Blaga; Mladenov, Boris; Rangelov, Simeon; Hammoudeh, Zora; Nesheva, Desislava; Staneva, Rada; Spasova, Viktoria; Grigorov, Evgeni; Hadjidekova, Savina; Slavov, Chavdar; Toncheva, Draga
Abstract: Many bladder cancer (BC) patients with early disease are asymptomatic and diagnosed at advanced stage when the therapeutic options are limited. This necessitates the development of reliable predictive molecular biomarkers that will ensure a positive therapeutic response in every patient. The aim of this study was to screen for alterations in gene expression levels related to drug sensitivity and resistance that may be further explored as potential predictive therapeutic biomarkers. Gene expression analysis of the 168 genes from two panels for Cancer drug resistance and metabolism (PAHS004) and Cancer Drug Targets (PAHS507z) was performed. A total of 47 transitorial cell bladder cancer samples of stage pTa, pT1, pT2 were investigated using the pooling method, which allows reducing the effect of biological variation and detecting only significant expression changes. Differential gene expression was calculated using the ΔΔCt method with GPDH as a housekeeping gene. The 4.0-fold change in gene expression was used as the cut-off threshold to determine upregulation or downregulation compared to normal bladder tissue (negative control). Significance of the differences in the expression profiles was assessed by nonparametric one-way analysis of variance (ANOVA) with Dunn's multiple comparison tests and Mann-Witney test. We demonstrated a correlation of tumor invasion and several up-regulated genes related to chemotherapy resistance. For the first time, this study demonstrated overexpression of CDK8, CDK9, FIGF, HDAC11, IGF1 and PDGFRA genes in muscle-invasive bladder carcinomas. These genes and their proteins could be used as potential biomarkers for bladder cancer progression or prospective therapeutic targets.